Hindu Kaharingan Dan Kerukunan Multikultural Di Kota Palangka Raya Kalimantan Tengah - Susi, Susi; yoppie, yoppie (Fakultas Dharma Duta, 2025)
His paper examines the transformation of Hindu Kaharingan and its strategic role in fostering interreligious harmony within the multicultural society of Palangka Raya, Central Kalimantan. Hindu Kaharingan, originally the traditional belief system of the Dayak people, was formally integrated into Hinduism in the 1980s to gain administrative recognition, thereby creating a dual identity that blends local spirituality with formal religious structures. Employing a systematic literature review and a theoretical-critical approach with interdisciplinary analysis, this study aims to synthesize findings on the function of Hindu Kaharingan as a socioreligious actor. The research demonstrates that infrastructures such as Balai Basarah and the institutional body Majelis Besar Agama Hindu Kaharingan (MB-AHK) serve as key platforms for dialogue, cultural preservation, and social integration through rituals and interfaith collaboration. Despite facing challenges such as politicization and shifts in the values of younger generations, the community exhibits resilience by revitalizing traditions and leveraging digital media. Consequently, this paper argues that Hindu Kaharingan occupies a strategic position in shaping inclusive social structures and makes a significant contribution to the discourse on local religions, identity politics, and cultural diversity in Indonesia.